2014
DOI: 10.3109/14992027.2014.920110
|View full text |Cite
|
Sign up to set email alerts
|

Ambient noise impact on accuracy of automated hearing assessment

Abstract: Ambient noise typical of that found in a non-sound-treated room, did not affect the accuracy of air conduction hearing thresholds obtained with the KUDUwave. The KUDUwave may be a viable method of testing when a clinical audiometer and sound booth are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 12 publications
7
60
4
Order By: Relevance
“…This shows that for approximately 95% of participants in this study the additional variation introduced was within an additional 5 dB absolute difference (±2.5 dB relative difference) of ISO standards. It is also comparable to previous clinical validation studies of the KUDUwave which showed 91% accuracy (Swanepoel et al, 2010) and 92% accuracy (Storey et al, 2014) of obtaining hearing thresholds within a 10 dB absolute difference in sound-treated and 40 dBA multi-talker background noise environments.…”
Section: Accuracysupporting
confidence: 74%
See 4 more Smart Citations
“…This shows that for approximately 95% of participants in this study the additional variation introduced was within an additional 5 dB absolute difference (±2.5 dB relative difference) of ISO standards. It is also comparable to previous clinical validation studies of the KUDUwave which showed 91% accuracy (Swanepoel et al, 2010) and 92% accuracy (Storey et al, 2014) of obtaining hearing thresholds within a 10 dB absolute difference in sound-treated and 40 dBA multi-talker background noise environments.…”
Section: Accuracysupporting
confidence: 74%
“…Whilst the additional 5 dB variation above the ISO standard may be considered low once the confounding factors are accounted for, the accuracy of automated audiometry in this study is lower than previous studies which have fallen within the ISO standard threshold variation limits Margolis et al, 2011;Storey et al, 2014;Swanepoel et al, 2010). Use of the same KUDUwave audiometer in manual-and automated mode, as in (Swanepoel et al, 2010), eliminates the calibration differences that were introduced in the present study, and could easily account for some of the increased differences in hearing thresholds.…”
Section: Accuracycontrasting
confidence: 48%
See 3 more Smart Citations